PENGEMBANGAN MEDIA PEMBELAJARAN KODEFIKASI REPRODUKSI, OBSETRI, PERINATAL DAN KONGENITAL BERBASIS MICROSOFT ACCESS DI STIKES DHARMA LANDBOUW PADANG - Mardiawati, Dewi; Ulfa, Mutia Mardha; Dewi, Siti Handam (Ensiklopedia of Journal, 2025)
System design aims to prepare a new/proposed system implementation plan. System design stage are carried out after the analysis stage, because after system analysis activities a system analyst has a clear picture of what must be idone. Thei aimi ofi thisi researchi isi toi findi outi thei design ofi coding learning media for chapters XIV, XV, XVI, XVII based on Microsoft Access at STIKESi Dharmai Landbouwi Padangi in 2024. This typei ofi researchi isi quantitative with a researchi method, namely researchi andi idevelopment, whichi willi bei carriedi outi at STIKES Dharma Landbouw Padang from March to June 2024. Thei populationi for thisi researchi isi 97 RMIK level 3 studentsi withi ai samplei of 14 istudents. Datai collectioni techniquesi werei carriedi outi usingi iquestionnaires, observationi andi simulation as well as collection tools, namely questionnaires, observation tables and simulation tables. Thei researchi resultsi showedi thati thei coding application hadi ai process flow with 5 steps and 5 required data components and was successfully executed well and was designed using a prototype and UML. This application was successfully run with an average ICD 10 code search time of 20.5 seconds. Basedi oni thei researchi iresults, iti cani bei concludedi thati thei coding application design was successfully tested by having the process flow and data components needed and making iti easieri fori students toi carryi outi coding andi saving time searching fori disease codes.Keywords: Design, Application, Coding, Microsoft Acces